Análise do potencial genotóxico e mutagênico de lodo de esgoto em Allium cepa - Martins, Maria Nilza Corrêa (2015)
The sewage sludge can contain high levels of inorganic and organic compounds with toxic, genotoxic and mutagenic properties. Its use in agricultural soils can be studied by the behaviour (or by the development and growth) of the different plant species relating to the toxic effects of this residue in different plant species. In a review it was possible to obtain data from the effects of the transfer of contaminants in soils supplemented with sewage sludge for plants and plants via the food chain. An organism test Allium cepa shows a positive response to this analysis of toxicity, that aimed to study the genetic toxicity of sewage sludge in Allium cepa. The experiment was conducted in the Laboratory of Morphology of the Center for Agricultural Sciences at the Federal University of Espírito Santo (CCA-UFES), in the municipality of Alegre, using seeds of Allium cepa treated with sludge from the ETE Jerônimo Monteiro and ETE Mulembá. The sludge were analysed with regard to physico-chemical and biological properties, according to the resolution CONAMA 375/2006. For the analysis of toxicity on the seeds of Allium cepa, 5.000 cells per treatment were evaluated by direct contact and trapped the samples and controls. The gross sludge presented physico-chemical results within the limits established by CONAMA resolution 375/2006. Only in the microbiological analysis the sludge of ETE of Jerônimo Monteiro presented fecal coliforms above the limit established by the resolution. For potential toxicity testing the sludge of ETE Jerônimo Monteiro was phytotoxic to raw sewage sludge, cytotoxic and genotoxic for sewage sludge solubilization. The gross sludge of ETE Mulembá presented genotoxic and mutagenic potential, while the sludge solubilized was cytotoxic. The sewage sludge with addition of lime presented potential phytotoxic to raw sludge, and for the sludge solubilized showed genotoxic and cytotoxic effect. The results were expressed as mean ± standard deviation. Statistical analysis was performed using the nonparametric test of Kruskal-Wallis (p < 0.05). It is concluded that both sludge have toxic potential, serving warning to their use in agricultural soils, which should be monitored with cytogenetic analyses and control of toxic elements present in its composition.